Aromaterapia e Ansiedade: revisão integrativa da literatura - Domingos, Thiago da Silva [UNESP]; Braga, Eliana Mara [UNESP] (My University, 2013)
This study aimed at investigating, in the national and international scientific literature, how aromatherapy is used as a therapeutic tool to reduce anxiety. It is a bibliographic study that adopted integrative literature review as a method. Studies published on databases Scielo, Medline and Cinahl from 2008 to 2012 were selected. A sample of 20 scientific articles was analyzed, and of these, 13 had an experimental and a quasi--experimental design whereas 07 were systematic or integrative reviews. The synthesis of knowledge sho-wed that aromatherapy represents a safe therapeutic practice although it is still underestimated in health care practices. The construction of evidence levels was not possible due to discrepancies in the studied populations, in research designs, the various essential oils used and the different methods for aromatherapy application. The knowledge gaps identified in these studies are related to the need to develop new forms to evaluate the effectiveness of this practice, including the therapist-patient relationship and the different communication forms that are intrinsic to aromatherapy.

O presente estudo teve como objetivo investigar na literatura científica nacional e internacional como se utiliza a aromaterapia como ferra-menta terapêutica para a redução da ansiedade. Trata-se de uma pes-quisa bibliográfica que adotou como método a revisão integrativa da literatura. Foram selecionados estudos publicados entre 2008 e 2012, nas bases de dados Scielo, Medline e Cinahl. A análise se constituiu de uma amostra de 20 artigos científicos, sendo 13 com delineamento ex-perimental e quase experimental e 07 revisões sistemáticas ou integra-tivas. A síntese do conhecimento permitiu afirmar que a aromaterapia representa uma prática terapêutica segura, embora ainda subestimada nas práticas de cuidado em saúde. A construção dos níveis de evidência ficou inviabilizada devido às discrepâncias nas populações estudadas, nos delineamentos das pesquisas, nos diversos óleos essenciais utiliza-dos e nos diferentes métodos de aplicação da aromaterapia. As lacunas de conhecimentos identificadas nestas pesquisas versam sobre a neces-sidade de desenvolvimento de novas formas de avaliação da efetividade desta prática, incluindo a relação terapeuta-paciente e os diferentes mo-dos de comunicação intrínsecos à aromaterapia.
Aromatherapy and Anxiety: integrative literature review
Keywords: Anxiety; Aromatherapy; Complementary therapies; Ansiedade; Aromaterapia; Terapias complementares